PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2018 - Murfat Effendi, Ery Setiyawan Ivana Nina Esterlin Barus2 (EKONOMIA, 2021)
The problems in this study are as follows: (1) is the Debt to Equity ratio (DER), Net Profit Margin (NPM), Current Ratio (CR), Inventory Turnover (ITO) partially and simultaneously affecting the share price of the Automotive companies and components listed on the Indonesia Stock Exchange period 2013 – 2018.       This research is conducted with the aim to know the influence of Debt to Equity Ratio (DER), Net Profit Margin (NPM), Current Ratio (CR) and Inventory Turn Over (ITO) to the price of shares in automotive companies and components listed on the stock Exchange Indonesia period 2013-2018. The method used for analyzing is a method of double linear regression analysis with the computerized program SPSS.       The results of research analysis show that both NPM and ITO have significant effect on stock prices in automotive companies and components listed on the Indonesia Stock exchange period of 2013-2018 while DER and CR have no effect, Evidenced by the results of the significance value DER (0,329 > 0,05), NPM (0,12 < 0,05), CR (0,522 > 0,05) and ITO (0,001 < 0,05).       The results of simultaneous research that the Debt to Equity Ratio (DER), Net Profit Margin (NPM), Current Ratio (CR) and Inventory Turn Over (ITO) have significant effect on the price of shares in automotive companies and components listed on the Indonesia stock Exchange Period 2013-2018, evidenced by the results of F countdown > F tabel and of the significance value (6,161 > 2,51).